Physiotherapy management in patients with pleural effusion: a systematic review - Dube, Saambhavi I.; Gunjal, Sambhaji (International Journal of Research in Medical Sciences, 2024)
Pleural effusion is the accumulation of fluid in between the parietal and visceral pleura, which is called the pleural cavity. It can occur by itself or can be the result of surrounding parenchymal disease like infection, malignancy, or inflammatory conditions. Pleural effusion is one of the major causes of pulmonary mortality and morbidity. With the aim to review the physiotherapy management in pleural effusion till date A Systematic review was done according to PRISMA guidelines was conducted on 15 articles through different databases like PubMed, google scholar which were identified, sorted, and screened according to the inclusion criteria and exclusion criteria post which the studies were assessed for quality. In this review the result data from the selected studies were extracted under the headings of title/author, type of study design, intervention /device /technique elaborated in the study, and key highlights of the study and was tabulated systematically. Following the discussion of results about the methods, effects of the protocols along with the biases in research it was concluded that Physiotherapy management increases pulmonary function, chest expansion and oxygenation in patients with pleural effusion.